Perancangan Algoritma untuk Menghitung Harga Opsi Reset dengan Metode Binomial - Bony Parulian Josaphat (Jurnal Aplikasi Statistika & Komputasi Statistik, 2015)
Reset option is one of exotic options or path-dependent options, namely his payoff option depends on the behavior of the price of the underlying asset between the beginning and the time to maturity, not solely depend on the final price of the underlying asset. Reset option discussed here is the reset option with single reset time . Based on the presence or absence of early exercise facility, reset option consists of an option of European and American.This paper describes the design of algorithms for reset option price calculation using binomial method. Furthermore, in this paper also described the algorithm implementation. Algorithm implementation is done by developing a simple application using Java programming language. After implementing and testing, we obtain results that the designed algorithm is fairly accurate based on a comparison with the results of similar calculation using Ms. Excel .